Influence of powder/liquid ratio on the radiodensity and diametral tensile strength of glass ionomer cements (Journal of Applied Oral Science, 2010)
Clinicians tend to make reductions in glass ionomer power/liquid (P/L) ratios since some materials are difficult to mix and flow into small cavities, grooves or pits. In general, changing the P/L ratio decreases the physical and mechanical properties of conventional glass ionomer cements (GICs) and resin modified glass ionomer cements (RMGICs), but alterations seem to depend on their composition. OBJECTIVE: To determine the influence of P/L ratio on the radiodensity and diametral tensile strength (DTS) of glass ionomer cements. MATERIAL AND METHODS: There were 2 factors under study: P/L ratio (manufacturer's recommended P/L ratio and a 50% reduced P/L ratio), and materials (Vitro Molar, Vitro Fil, Vitro Cem conventional GICs and Vitro Fil LC, Ortho Glass LC RMGICs. Five 1-mm-thick samples of each material-P/L ratio were produced for radiodensity evaluation. Samples were x-ray exposed onto Digora phosphor plate and radiodensity was obtained using the software Digora for Windows 2.5 Rev 0. For DTS, five (4.0x8.0 mm) cylinder samples of each material were tested (0.5 mm/min). Data were subjected to one- and two-way ANOVA (5x2) followed by Tukey's HSD test, or Kruskal-Wallis and Dunn's method. For paired comparisons, t-test or Mann-Whitney test were used (α=0.05). RESULTS: There was a significant interaction (P=0.001) for the studied factors (materials vs. P/L ratio). Reduced P/L ratio resulted in significantly lower DTS for the RMGICs, but radiodensity was affected for all materials (P